Factor because if we have
yz=0 then we can assume y and/or z=0
so factor
so the easiest way is to find what 2 numbers add to -6 and multiply to get 9 so
we know that they must be both - because we must have x+x=(-) and x^2=+ so therefor they must be negative
factors of 9=3 and 3 so
-3 and -3
-3+-3=-6 perfect
(z-3)(z-3)=0
set each to zero
z-3=0
add 3
z=3
z=3 is the answer
Answer:
From least to greatest: -2, 2/3
Step-by-step explanation:
Set each factor equal to 0 and solve
2x + 4 =0
2x = -4
x = -2
3x - 2 = 0
3x = 2
x = 2/3
Answer:
1.23
2.60
3.45
4.37.524 (Im not incredibly posotive ab this one)
5.28
Step-by-step explanation:
Distribute 3 throught the parentheses
Move the variable to the left-hand side and change its sign
Move the constant to the right-hand side and change its sign
Collect like terms
Divide both sides of the equation by -3